Evaluating the prognostic relevance of neutrophil-to-lymphocyte ratio in cervical cancer: a systematic review and meta-analysis - Zhuang, Xieyan; Li, Yan; Zheng, Hongfeng; Fu, Langjing (Frontiers in Oncology, 2024)
BackgroundRecently, the neutrophil-to-lymphocyte ratio (NLR) has emerged as a promising prognostic marker for survival outcomes in individuals affected cervical cancer. However, research specifically focusing on the prognostic relevance of NLR across different cancer stages and in cases of recurrent metastases remains scant.MethodsWe executed a systematic review of the literature from databases including PubMed, Embase, the Cochrane Library, and Web of Science, covering publications up to March 3, 2024. Studies evaluating the relationship between NLR and patient clinical outcomes were retrieved, guided by specifically defined inclusion and exclusion parameters. The key goals were to assess progression-free survival (PFS) and overall survival (OS), measured through hazard ratios (HR) and 95% confidence intervals (CI).ResultsThis meta-analysis encompassed 38 retrospective cohort studies, including data from 10,246 patients. The aggregated data showed that patients with increased NLR prior to treatment exhibit reduced OS (HR = 1.58, 95% CI: 1.44-1.74; p < 0.00001) and decreased PFS (HR = 1.48, 95% CI: 1.34-1.63; p < 0.00001). Furthermore, elevated NLR significantly impacted disease-free survival (HR: 1.79, 95% CI: 1.18-2.71; p = 0.006), recurrence rates (HR: 2.18, 95% CI: 1.36-3.51; p = 0.001), recurrence-free survival (HR: 3.05, 95% CI: 1.79-5.19; p < 0.0001), and the incidence of distant metastases (HR: 1.73, 95% CI: 1.20-2.50; p = 0.003).ConclusionAn elevated NLR prior to treatment demonstrates a strong association with decreased OS and PFS among patients with cervical cancer, underscoring the significance of NLR as a prognostic marker within this population.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=529817, identifier CRD42024529817.